Flipped Classroom Models: Revolutionizing Learning in Higher Education - Aceng Haetami; Abena Boateng; Ricardo Martinez (Yayasan Adra Karima Hubbi, 2025)
Background. The traditional lecture-based model of teaching in higher education has faced increasing criticism due to its limited engagement and ability to foster active learning. In response, the flipped classroom model has emerged as a promising alternative, where students engage with instructional content outside the classroom and use class time for collaborative and interactive activities. Purpose. This study aims to investigate the effectiveness of flipped classroom models in higher education, focusing on their impact on student engagement, academic performance, and learning outcomes. Method. A mixed-methods approach was employed, combining quantitative analysis of student performance data with qualitative insights from surveys and interviews. A sample of 200 students from five different universities participated in flipped classroom courses, and their learning outcomes were compared to those of students in traditional lecture-based courses. Data were collected at the beginning and end of the semester to assess changes in engagement and academic performance. Results. The study found that students in flipped classrooms showed significantly higher levels of engagement and academic performance compared to their peers in traditional settings. Students reported increased satisfaction with the learning process, particularly in terms of collaborative learning and self-paced study. Conclusion. The flipped classroom model proves to be an effective strategy for enhancing student engagement and improving learning outcomes in higher education.